Translational Approach to Predicting the Efficacy of Maraviroc-Based Regimens as HIV Preexposure Prophylaxis - Srinivas, Nithya (Antimicrob Agents Chemother, 2020)
Maraviroc-based regimens have been explored as preexposure prophylaxis (PrEP) against human immunodeficiency virus (HIV). In this study, we utilized mucosal tissue drug exposure data, combined with target concentrations generated in vitro, in a pharmacokinetic-pharmacodynamic analysis to predict the effects of drug combinations and adherence on PrEP efficacy. Mucosal tissue concentrations of maraviroc were measured in 24 healthy women. The 90% effective concentrations (EC(90)) of maraviroc (alone and combined with tenofovir and emtricitabine) for protection against HIV were identified in CD4(+) T cells. Monte Carlo simulations were performed to identify dosing strategies to protect colorectal and female genital tract (FGT) tissues from HIV infection. Colorectal maraviroc concentrations were 350-fold higher than in the FGT. Under steady-state conditions, our model predicted that one 300-mg dose/week was sufficient to protect colorectal tissue from HIV in 99% of the population, while 300 mg daily would protect the FGT in only 63% of the population. FGT protection increased to >90% when maraviroc was used in combination with tenofovir (5 doses/week) or emtricitabine (3 doses/week). Poor adherence resulted in a drastic decrease in efficacy in the FGT but not colorectal tissue. However, greater forgiveness was seen when maraviroc was combined with tenofovir or emtricitabine, suggesting that maraviroc should not be used alone as PrEP.